A hybrid model of type-4 wind turbine - Concept and implementation for power system simulation; Innovative Smart Grid Technologies Conference Europe (ISGT Europe), IEEE PES - Andreev M. V. Mikhail Vladimirovich; Razzhivin I. A. Igor Andreevich; Suvorov A. A. Aleksey Aleksandrovich; Ruban N. Yu. Nikolay Yurievich; Ufa R. A. Ruslan Alexandrovich; Gusev A. S. Alexander Sergeevich; Bay Yu. D. Yuly Dmitrievich; Kievets A. V. Anton Vladimirovich; Askarov A. B. Alisher Bakhramzhonovich; Rudnik V. E. Vladimir Evgenevich (2020, 2020)
Title screen